Simple generation of various α-monofluoroalkyl radicals by organic photoredox catalysis: modular synthesis of β-monofluoroketones. Issue 21 (25th February 2021) - Taniguchi, Ryo; Noto, Naoki; Tanaka, Seiya; Takahashi, Keigo; Sarkar, Sujan K.; Oyama, Ryoko; Abe, Manabu; Koike, Takashi; Akita, Munetaka
Abstract : A novel and simple strategy for radical α-monofluoroalkylation by organic photoredox catalysis has been developed. Abstract : A metal-free and operationally simple strategy for the generation of various α-monofluoroalkyl radicals has been developed. A combination of 1, 4-bis(diarylamino)naphthalene photocatalyst and sulfoximine-based fluoroalkylating reagents is the key to success. The protocol can be applied to modular synthesis of β-monofluoroketones through radical monofluoroalkylation of alkenyl acetates.